Aerodynamic characteristics of medium-low-speed maglev trains during intersection in two-track tunnel - JIAO Qizhu; ZHANG Mingju; XIONG Xiaohui; WANG Kaiwen; CHEN Bo (机车电传动)
In order to investigate pressure variations on both the tunnel wall and train body surface when 140 km/h medium-low-speed maglev trains intersect in two-track tunnels, numerical calculations were performed, focusing on the effects of different parameters of the train/tunnel on the aerodynamic performance of the tunnel wall and train body surface. Moreover, a comparison was conducted across different train consist lengths and various tunnel clearance areas to assess their effects on internal train pressures. The results indicated an inversely proportional relationship between the peak value of pressure variations at measuring points on the tunnel wall and the 1.379th power of the tunnel clearance area, as well as between the peak value of pressure variations at measuring points on the train body surface and the 1.231st power of the tunnel clearance area during the intersection of 4-car maglev trains in the middle section of two-track tunnels. Additionally, under an airtightness index of 0.5 s, the pressure variations over 3 s at measuring points inside 8-car trains resulting from the intersection in tunnels with a tunnel clearance area of 66.2 m2 increased by 102.2%, compared with the 4-car scenarios. Under an airtightness index of 8 s, this figure decreased to 50.4%. The study findings of this paper provide a reference basis for the construction of tunnels to accommodate the operation of medium-low-speed maglev trains.